Liability of Indonesian Airlines for Refunds Due to Flight Cancellations Under Consumer Protection Law - Panggabean, Azra; Anggusti, Martono; Siregar, Ria (Indonesian Journal of Law and Justice, 2025)
Flight cancellations often cause losses to consumers, both materially and immaterially, and cause uncertainty about the rights and amount of compensation in accordance with the regulations. This study aims to analyze the liability of Indonesian airlines in flight cancellations based on consumer protection regulations and the suitability of the airline's internal policies with applicable regulations. The method used is normative juridical research with a literature study approach. Primary legal materials include Consumer Protection Law No. 8 of 1999, Law No. 1 of 2009 concerning Aviation, as well as Ministerial Regulations PM 77/2011, PM 89/2015, and PM 30/2021. Secondary legal materials include internal airline policies, books, journals, and relevant legal literature. The analysis technique used is qualitative analysis with a descriptive approach. The results show that the internal policies of Indonesian airlines are generally in line with the laws and regulations related to flight cancellation. However, there are still some aspects that require optimization in the implementation of compensation and transparency of information to consumers. This regulatory alignment is expected to improve consumer protection, legal certainty, and the quality of airline services in handling flight cancellations.